The Impact of Human Resource Management Practices on Operational Performance at Ginta Cargo Lombok - Ridha Nurul Hayati; Dina Novita; Rudi Wibowo (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study examines the impact of Human Resource Management (HRM) practices on operational performance at Ginta Cargo Lombok, identifying key HRM dimensions that contribute to operational effectiveness in a regional logistics firm. Research Methodology: A quantitative causal survey design was applied to 84 active employees. Data were collected using structured Likert-scale questionnaires and secondary operational records. Multiple linear regression was employed to test the effects of recruitment and selection, training and development, reward systems, and internal communication on operational performance. Results: The results show that HRM practices significantly influence operational performance, explaining 58% of the variance. Training and development had the strongest positive effect, followed by reward systems. Recruitment and selection, and internal communication, although significant, had moderate effects on performance. Conclusions: Integrated HRM practices aligned with performance goals are essential for improving efficiency, accuracy, and service speed in regional logistics firms. Effective HRM practices enable employees to contribute to the company’s operational success. Limitations: This study is limited to a single branch and relies on self-reported data, which may introduce bias. The sample size is relatively small, and the findings may not fully generalize to other locations or logistics firms. Contributions: This study provides empirical evidence on the significance of integrated HRM practices in enhancing operational performance within the logistics industry. It highlights how HRM practices, when strategically aligned, play a crucial role in boosting the performance of regional logistics firms.